The values campaign? : the Christian right and the 2004 elections - Green, John Clifford, 1953-; Rozell, Mark J.; Wilcox, Clyde, 1953- (Religion and politics series (Georgetown University), 2006)
The Christian Right never ceases to surprise professional observers of American politics. With the Christian coalition in disarray, many expected that the movement would play less of a role in the 2004 elections. But when exit polls reported that moral values were the most commonly cited reason for presidential vote choice, pundits immediately proclaimed the importance of the values vote. Yet the role of the Christian Right, of statewide referenda on same-sex marriage, and of religious mobilization remained the subject of debate. The Values Campaign? The Christian Right and the 2004 Elections r.